PENGARUH FASILITAS KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) PEGAWAI KELURAHAN - Rudi Asrul Hakim; Mhd. Ikhwanda Nawawi; Awaluddin Napitupulu; Agung Mariani Barus (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
This study will analyze the effect of work facilities on organizational citizenship behavior of employees of Tanjung Rejo Village, Medan Sunggal Subdistrict, Medan City. This study uses a quantitative method by distributing questionnaires through google form to the whats up group of Tanjung Rejo sub-district employees, amounting to 35 people, and employees who fill out the questionnaire, namely 33 people. The job satisfaction of the Tanjung Rejo sub-district employees also turns out to be able to motivate the employees of the Tanjung Rejo Village in a positive way where the increase in employee job satisfaction will increase the employee's motivation to work. So that OCB also increases indirectly. Because there is satisfaction with high salaries, satisfaction with rewards, employee placement according to their skills, various types of work and levels of difficulty that make employees feel challenged will increase employee motivation.